Do Enhanced Funding Policies Targeting Students in Poverty Close Achievement Gaps? Evidence from the American States, 1996–2015. Issue 3 (7th November 2019) - Thorson, Gregory R.; Gearhart, Sera M.
Abstract : Public concern stemming from the wide disparities in academic achievement based on student poverty status extends back at least to the issuing of the Coleman Report in 1966. The Coleman Report found large and persistent achievement gaps between economic and racial subgroups, yet, perhaps surprisingly, did not find large gaps in funding. The achievement gaps identified in the Coleman Report persist today. Since the NCES began tracking poverty gaps with the National Assessment of Education Progress (NAEP) in the 1990s, the disparities in achievement based on poverty have been large and statistically significant. In response, many states began enacting school funding mechanisms to direct additional resources to high‐poverty schools. Currently, 41 states have employed funding enhancements for poor students (EdBuild, 2018). Are these mechanisms effective at reducing the disparity in achievement for poor versus non‐poor students? Using data from the Urban Institute (2017), we find that states that have directed additional resources towards poor students effectively reduced the disparity between poor and non‐poor students in NAEP fourth‐ and eighth‐grade math and reading exams. Whereas the results are large and statistically significant, the costs associated with fully eliminating the disparity between poor and non‐poor students are very high. Abstract : 因基于学生贫困情况的巨大学术成就差异而产生的公共关切至少能追溯到1966年《科尔曼报告》（以下简称《报告》）的发行。《报告》发现经济子群和种族子群之间存在巨大且持续的学术成就差距，然而出乎意料的是，《报告》并未发现经费中存在的巨大差距。《报告》所识别的学术成就差距在今天仍然存在。自20世纪90年代起美国国家教育统计中心（NCES）与国家教育进展评估（NAEP）开始追踪贫困差距，发现基于贫困的学术成就差距一直是巨大的、显著的。许多州的回应方式则是开始制定学校经费机制，将额外资源引入高度贫困学校。目前41个州已为贫困学生提高了经费（EdBuild 2018）。这些机制在减少贫困学生与非贫困学生的学术成就差距一事上是有效的吗？通过使用城市研究所（Urban Institute 2017）的数据，我们发现，就将额外资源给予贫困学生的各州而言，NAEP四年级和八年级数学测验与阅读测验中贫困学生与非贫困学生的学术成就差异得到了有效的减少。虽然结果是明显的、显著的，但完全消除贫困学生与非贫困学生之间的差距，所需的成本极高。 Abstract : La preocupación pública derivada de las grandes disparidades en el rendimiento académico basado en el estado de pobreza de los estudiantes se remonta al menos a la publicación del Informe Coleman en 1966. El informe de Coleman encontró grandes y persistentes brechas de logros entre los subgrupos económicos y raciales, pero, quizás sorprendentemente, no encontró grandes brechas en la financiación. Las brechas de logros identificadas en el Informe Coleman persisten hoy. Desde que el NCES comenzó a rastrear las brechas de pobreza con la Evaluación Nacional del Progreso Educativo (NAEP) en la década de 1990, las disparidades en los logros basados en la pobreza han sido grandes y estadísticamente significativas. En respuesta, muchos estados comenzaron a promulgar mecanismos de financiación escolar para dirigir recursos adicionales a las escuelas de alta pobreza. Actualmente, 41 estados han empleado mejoras de financiación para estudiantes pobres (EdBuild 2018). ¿Son efectivos estos mecanismos para reducir la disparidad en el rendimiento de los estudiantes pobres versus los que no son pobres? Usando datos del Urban Institute (Urban Institute 2017), encontramos que los estados que han dirigido recursos adicionales hacia estudiantes pobres redujeron efectivamente la disparidad entre los estudiantes pobres y no pobres en los exámenes NAEP de matemáticas y lectura de 4to y 8vo grado. Si bien los resultados son grandes y estadísticamente significativos, los costos asociados con la eliminación total de la disparidad entre estudiantes pobres y no pobres son muy altos.